2005
DOI: 10.1007/s00259-005-1866-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of an increase in the serum thyroglobulin level at the time of the first ablative radioiodine treatment in patients with differentiated thyroid cancer

Abstract: Our data show that the TgD5/TgD0 ratio may be used as a new prognostic indicator of (131)I treatment efficacy in patients with DTC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 13 publications
2
51
0
2
Order By: Relevance
“…A higher Tg ratio (>20) was related to ablation success despite a higher pre-ablation Tg level (≥5 ng/ml). Kim et al [7] also compared pre-ablation stimulated Tg levels with Tg ratios and the result was similar with that of Bernier et al [8].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A higher Tg ratio (>20) was related to ablation success despite a higher pre-ablation Tg level (≥5 ng/ml). Kim et al [7] also compared pre-ablation stimulated Tg levels with Tg ratios and the result was similar with that of Bernier et al [8].…”
Section: Discussionsupporting
confidence: 67%
“…Bernier et al [8] investigated the prognostic value of an increase in serum Tg in patients with DTC. Tg ratios were calculated by dividing post-ablation Tg (measured 5 days after RAI therapy) by pre-ablation Tg and compared with preablation serum Tg levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bernier et al studied the Tg values in patients just before and 5 days after RAI and concluded that having a TgD5/TgD0 ratio higher than 20 was significantly related to successful ablation [9]. Kim et al also studied 152 patients treated with rh-TSH and found that high elevation of Tg 3 days after RAI compared with preablative stimulated Tg was significantly related to successful ablation [20].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have also suggested that high levels of serum Tg at the time of RAI could be a prognostic marker for prediction of ablation failure [6][7][8][9]. Also, several studies have reported the serum Tg doubling time under thyrotropin suppression as a prognostic predictor in patients with DTC [10].…”
Section: Introductionmentioning
confidence: 99%